2013
DOI: 10.4238/2013.july.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α and -β genetic polymorphisms as a risk factor in Saudi patients with vitiligo

Abstract: ABSTRACT. Vitiligo is an acquired depigmentary disorder of the skin, characterized by multiple susceptibility loci and genetic heterogeneity. The etiology of vitiligo is unknown but several hypotheses, including an autoimmune origin, have been proposed. Tumor necrosis factor (TNF)-α, a pleiotropic proinflammatory cytokine, has been shown to play a critical role in several autoimmune diseases including vitiligo. The aim of present study was to determine the association of TNF-α and -β gene polymorphisms with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
4
22
1
Order By: Relevance
“…TNF-α and TNF-β genes were amplified using an amplification refractory mutation system-PCR methodology to detect any polymorphism involved at positions −308 of TNF-α and +252 in intron 1 of TNF-β gene. PCR amplification was carried out using PuReTaq Ready-to-Go PCR Beads (GE Healthcare, Buckinghamshire, UK) as described elsewhere 32. The molecular analysis of the samples was performed in the same laboratory and at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α and TNF-β genes were amplified using an amplification refractory mutation system-PCR methodology to detect any polymorphism involved at positions −308 of TNF-α and +252 in intron 1 of TNF-β gene. PCR amplification was carried out using PuReTaq Ready-to-Go PCR Beads (GE Healthcare, Buckinghamshire, UK) as described elsewhere 32. The molecular analysis of the samples was performed in the same laboratory and at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…Three were excluded because no extractable genotype data or family data were included. Thus, 15 studies met our inclusion criteria (Brinkman et al, 1997;Vinasco et al, 1997;van Krugten et al, 1999;Yen et al, 2001;Fabris et al, 2002;Zwiers et al, 2004;Correa et al, 2005;Rodríguez-Carreón et al, 2005;Yazici et al, 2006;Namian et al, 2009;Emonts et al, 2011;Laddha et al, 2012;Salinas-Santander et al, 2012;Al-Harthi et al, 2013;You et al, 2013). Ten studies examined RA and 5 examined vitiligo.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The TNF-a -238 A/G and -308 A/G polymorphisms have been reported to be associated with several autoimmune disorders (Lee et al, 2006). However, studies examining the associations between these polymorphisms and RA or vitiligo have shown conflicting results (Brinkman et al, 1997;Vinasco et al, 1997;van Krugten et al, 1999;Yen et al, 2001;Fabris et al, 2002;Zwiers et al, 2004;Correa et al, 2005;Rodríguez-Carreón et al, 2005;Yazici et al, 2006;Namian et al, 2009;Emonts et al, 2011;Laddha et al, 2012;Salinas-Santander et al, 2012;Al-Harthi et al, 2013;You et al, 2013). Persistent difficulties regarding robust and replicable results in genetic association studies are almost certainly attributable to the small size of the effects of genetic variants, and therefore, a large number of study subjects is required to ensure adequate statistical power, such as a meta-analysis.…”
Section: Tnf-α -238mentioning
confidence: 99%
“…The most common polymorphism occurs at position -308 (TNF-α-308G/A), which may affect the cytokine production (Wilson et al, 1997;Louis et al, 1998;Abraham and Kroeger, 1999). A number of case-control studies have been conducted to investigate the association between the TNF-α-308G/A polymorphism and vitiligo risk (Yazici et al, 2006;Namian et al, 2009;Laddha et al, 2012;Salinas-Santander et al, 2012;Al-Harthi et al, 2013;Aydingoz et al, 2015). However, the results of these studies have been inconsistent, which may be attributed to small sample sizes and the differences in ethnic populations.…”
Section: Introductionmentioning
confidence: 99%